Deterministic selection dominates microbial community assembly in termite mounds. (January 2021) - Chen, Qing-Lin; Hu, Hang-Wei; Yan, Zhen-Zhen; Li, Chao-Yu; Nguyen, Bao-Anh Thi; Sun, An-Qi; Zhu, Yong-Guan; He, Ji-Zheng
Abstract: Termite mounds are an important habitat for an enormous diversity of microorganisms. However, the microbial community assembly processes in termite mounds remain unresolved, which impeded our ability to predict the biological functions of these mound-associated microbiota under the global changes. Here we conducted a large-scale investigation in northern Australia to explore biogeographical patterns of microbial community in termite mounds and identify the role of deterministic and stochastic processes in microbial community assembly. Microbial communities in termite mounds exhibited a significant distance-decay pattern, and fungi had a stronger distance-decay relationship than bacteria. The neutral community model and normalized stochasticity ratio index ( NST ) revealed that the deterministic selection, rather than stochastic forces, predominated the microbial community assembly in termite mounds. Deterministic processes exhibited a significantly weaker impact on bacteria ( NST = 45.23%) than on fungi ( NST = 33.72%), likely due to the wider habitat niche breadth and higher potential migration rate of bacteria. Random forest model further demonstrated that mean annual temperature was the most important predictor of both bacterial and fungal profiles in termite mounds. These findings improved our understanding of spatial patterns and processes of microbiome in termite mounds, which is critical to decipher the role of termite mounds associated microbes in regulating ecosystem multifunctionality. Highlights: Termite mounds associated microbial communities exhibited a significant distance-decay pattern. Deterministic selection predominated the microbial community assembly in termite mounds. Mean annual temperature is the most important predictor of microbial profiles in termite mounds. Deterministic processes exhibited a weaker impact on bacteria than fungi.